2005
DOI: 10.1248/bpb.28.2289
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Mediated Cytotoxicity of Prodigiosin-Like Red Pigment Produced by .GAMMA.-Proteobacterium and Its Multiple Bioactivities

Abstract: A bacterial strain (MS-02-063), which produces red pigment, was discovered from our library established with more than 20000 microorganisms isolated from coastal area of Nagasaki prefecture, Japan. Comparison of 16S rDNA gene sequence of strain MS-02-063 with sequences from GenBank demonstrated that this strain belongs to the g-proteobacterium species. Recent our study has demonstrated that the highly purified red pigment showed potent antimicrobial activity against pathogenic microorganisms such as Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…The colony forming efficiency of the all cell lines used was between 90% and 95%. The cytotoxicity of the polysaccharides was also assessed using the Alamar blue assay, as described previously (19). In brief, adherent cells (2500-20,000 cells/well) were cultured in 96-well plates varying concentrations of polysaccharides in the growth medium for 48 h. Then, Alamar blue reagent was added to the cells at a final concentration of 10%.…”
Section: Measuring Cytotoxicity Of Ascophyllan and Fucoidan On Mammalmentioning
confidence: 99%
“…The colony forming efficiency of the all cell lines used was between 90% and 95%. The cytotoxicity of the polysaccharides was also assessed using the Alamar blue assay, as described previously (19). In brief, adherent cells (2500-20,000 cells/well) were cultured in 96-well plates varying concentrations of polysaccharides in the growth medium for 48 h. Then, Alamar blue reagent was added to the cells at a final concentration of 10%.…”
Section: Measuring Cytotoxicity Of Ascophyllan and Fucoidan On Mammalmentioning
confidence: 99%
“…In prelimi-nary studies, PG-L-1 led to the suppression of activation of NADPH oxidase in a macrophage cell line (data not shown). In addition, since no scavenging effect of PG-L-1 on ROS produced by hypoxanthine/xanthine oxidase system was observed (Nakashima et al 2005c), PG-L-1 may directly act on NADPH oxidaselike enzyme in C. marina. Detailed analyses of the effects of PG-L-1 on both NADPH oxidase in C. marina and macrophage cell lines are now in progress.…”
Section: Discussionmentioning
confidence: 89%
“…We suggested that the cytotoxic mechanism of PG-L-1 is the induction of apoptotic cell death through activation of p38 mitogen-activated protein kinase in human myeloid leukemia (U937) cells (Nakashima et al 2005c). Since PG-L-1 showed cytostatic activity against Chattonella marina, the cytotoxic mechanism of action of PG-L-1 against this raphidophyte may be different from that of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nilai ekonomis dan komersialisasi prodigiosin bersifat multifungsi, yaitu sebagai antibakteri, antifungi, antiprotozoal (Dhanasekaran et al, 2009), bersifat sitotoksik (Nakashima et al, 2005), antitumor (Castro, 1967;Pérez-Tomás et al, 2003), antimalaria, antidiabetes, antioksidan, obat-obatan, antiinflamasi non steroid, serta dapat juga menjadi pewarna untuk sutera dan wool (Khanafari et al, 2006). Produksi prodigiosin sangat bervariasi antarspesies dan strain Serratia, serta dipengaruhi oleh komposisi media dan waktu inkubasi.…”
Section: Pendahuluanunclassified